Preoperative Neutrophil to Lymphocyte Ratio Predicts Complications After Esophageal Resection That can be Used as Inclusion Criteria for Enhanced Recovery After Surgery - Shi, Bo-Wen; Xu, Li; Gong, Chun-Xia; Yang, Fu; Han, Yu-Dong; Chen, He-Zhong; Li, Chun-Guang (Frontiers in Surgery, 2022)
Background The neutrophil to lymphocyte ratio (NLR) has been reported as an indicator for poor prognosis in many cancers including esophageal cancer. However, the relationship between the NLR and postoperative complications after esophageal cancer resection remains unclear. At present, enhanced recovery after surgery (ERAS) lacks inclusion criteria. The aim of this study is to determine whether the preoperative NLR (preNLR) can predict complications after esophageal cancer resection, which could represent the criteria for ERAS. Methods This was a retrospective study on 171 patients who underwent esophagectomy at Hospital between November 2020 and November 2021(68 patients from Changhai Hospital, 65 patients from Shanghai General Hospital and 38 patients from Affiliated Hospital of Qingdao University). Univariate and multivariate logistic regression analyses were performed to demonstrate that the preNLR could predict complications after esophagectomy. Results A preNLR cutoff value of 2.30 was identified as having the greatest ability to predict complications with a sensitivity of 76% and specificity of 65%. Moreover, the Chi-squared test results showed that the preNLR was significantly associated with complications (x2=13.641, p<0.001), and multivariate logistic regression analysis showed that body mass index (BMI), p stage and preNLR were independent variables associated with the development of postoperative complications (p<0.05). Conclusion The preNLR can predict complications after esophagectomy, and these predicted complications can represent the criteria for recruiting patients for ERAS.